Antineoplasctic effects of bortezomib in cellular spheroids from endothelial cells transformed by kaposi sarcoma-associated herpes virus g protein coupled receptor - Suares, Alejandra Carolina (2017)
The Kaposi’s Sarcoma-associated Herpes virus G Protein-Coupled Receptor (vGPCR) is a key molecule in the pathogenesis of Kaposi sarcoma. Persistent expression and activity of vGPCR is required for NFkB pathway activation and tumor maintenance in endothelial cells. We have previously demonstrated that Bortezomib (BTZ, 0.5 nM) inhibits vGPCR cell growth by MKP-3 accumulation, a of this phosphatase reduces ERK1/2 and FOXO1 phosphorylation. In turn, ERK1/2 inhibition reduces VEGF expression and FOXO1 activation promotes p21 induction. All these events converge in the inhibition of cell proliferation. Many types of mammalian cells can aggregate and differentiate into 3-D multicellular spheroids (MCS) when cultured in suspension or in a non-adhesive environment. Compared to conventional mono-layer cultures (2D-cultures), MCS resemble real tissues better in terms of structural and functional properties. Multicellular spheroids formed by transformed cells are widely used as avascular tumor models for metastasis and invasion research and for therapeutic screening. In the present work, we develop the technique to obtain MCS from vGPCR cells in order to test whether MCS respond similar to 2D-cultures. To that end, MCS were treated with BTZ (0-2.5 nM) for 48 h. Results from Western blot analysis showed that BTZ decreases ERK1/2 protein phosphorylation, while MKP-3 protein levels are increased. Moreover, qRT-PCR studies revealed that p21 gene expression is also increased. All together, these results suggest that MCS of vGPCR cells treated with BTZ respond likewise those treated in 2D-cultures of vGPCR cells, but a higher dose.